A Prospective Clinical and Radiological Evaluation at 5 Years After Arthroscopic Matrix-Induced Autologous Chondrocyte Implantation. (January 2017) - Ebert, Jay R.; Fallon, Michael; Wood, David J.; Janes, Gregory C.
Background: While midterm outcomes after matrix-induced autologous chondrocyte implantation (MACI) are encouraging, the procedure permits an arthroscopic approach that may reduce the morbidity of arthrotomy and permit accelerated rehabilitation. Hypothesis: A significant improvement in clinical and radiological outcomes after arthroscopic MACI will exist through to 5 years after surgery. Study Design: Case series; Level of evidence, 4. Methods: We prospectively evaluated the first 31 patients (15 male, 16 female) who underwent MACI via arthroscopic surgery to address symptomatic tibiofemoral chondral lesions. MACI was followed by a structured rehabilitation program in all patients. Clinical scores were administered preoperatively and at 3 and 6 months as well as 1, 2, and 5 years after surgery. These included the Knee injury and Osteoarthritis Outcome Score (KOOS), Lysholm knee scale (LKS), Tegner activity scale (TAS), visual analog scale for pain, Short Form–36 Health Survey (SF-36), active knee motion, and 6-minute walk test. Isokinetic dynamometry was used to assess peak knee extension and flexion strength and limb symmetry indices (LSIs) between the operated and nonoperated limbs. High-resolution magnetic resonance imaging (MRI) was performed at 3 months and at 1, 2, and 5 years postoperatively to evaluate graft repair as well as calculate the MRI composite score. Results: There was a significant improvement ( P < .05) in all KOOS subscale scores, LKS and TAS scores, the SF-36 physical component score, pain frequency and severity, active knee flexion and extension, and 6-minute walk distance. Isokinetic knee extension strength significantly improved, and all knee extension and flexion LSIs were above 90% (apart from peak knee extension strength at 1 year). At 5 years, 93% of patients were satisfied with MACI to relieve their pain, 90% were satisfied with improving their ability to undertake daily activities, and 80% were satisfied with the improvement in participating in sport. Graft infill ( P = .033) and the MRI composite score ( P = .028) significantly improved over time, with 90% of patients demonstrating good to excellent tissue infill at 5 years. There were 2 graft failures at 5 years after surgery. Conclusion: The arthroscopically performed MACI technique demonstrated good clinical and radiological outcomes up to 5 years, with high levels of patient satisfaction.